Confirmatory Factor Analysis of Emotional Management Instrument in Indonesian Futsal Players - Wawan Sundawan Suherman; Soni Nopembri; Sigit Dwi Andrianto; Fitri Agung Nanda; Dewi Nurhidayah; Novriansyah Novriansyah; José Vicente García-Jiménez (Journal of Coaching and Sports Science, 2025)
Background: Emotional management is a key psychological factor influencing futsal performance, but available measurement instruments are still general in nature, lack sport-specific validation, and have not been tested on Indonesian futsal athletes. Aims: This study seeks to rigorously validate and confirm the factor structure of an emotional management instrument designed explicitly for Indonesian futsal athletes, thereby strengthening its scientific and contextual relevance calculations with CFA. Methods:  Confirmatory Factor Analysis (CFA) was performed on data from 438 athletes recruited through incidental sampling across multiple regions in Indonesia. The emotional management instrument comprised 23 items that had previously undergone rigorous content validation by experts, including psychologists, national-level futsal coaches, and sport science academics. Model fit indices, convergent validity, and internal consistency reliability were systematically evaluated to ensure the robustness of the measurement model. Results: The five-factor model demonstrated excellent fit to the data (e.g., CFI > .95, TLI > .95, RMSEA < .06, SRMR < .08). All factors had AVEs above 0.50, indicating strong convergent validity. Reliability indices were high, with McDonald's ω and Cronbach's α exceeding .70 for all factors. Conclusion: The results indicate that the emotional management instrument demonstrates satisfactory validity, reliability, and structural integrity for application among Indonesian futsal athletes, thereby providing a robust framework for psychological assessment and supporting future research, talent development, and mental training programs.